CORRELATION BETWEEN PERSONNEL’ AUTHENTICITY IN THE WORKPLACE, BURNOUT AND WELL-BEING - Vīra, Raina; Pīpkalēja, Linda; Blumberga, Solveiga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
To be authentic is to be oneself, needs, true and original, to be aware of one's identity, to act in accordance with values, needs and desires, which naturally contributes to quality of life. Well-being is a universal life goal and one of the most important strategic priorities and human resource trends in organizations today. A large part of people's lives is spent at work, which today is characterized by uncertainty, competitiveness, and stress, so it is in the interest of organizations to contribute authentic expressions in their employees, making them feel better and thus more productive, while attracting new talents who value authenticity at work as a psychological benefit. The aim of the research is to explore personnel’ authenticity in the workplace in relation to burnout and well-being and to develop proposals to human resource managers and managers for enhancing personnel’ authenticity and well-being and reducing burnout. Three research questions: Are there correlations between personnel' authenticity in the workplace, burnout, and well-being; Are there differences in variables between age groups, by organization size, between seniority groups and different types of work models; Does authenticity in the workplace affect burnout and well-being. The following methods were used: Relational Authenticity Questionnaire; Maslach Burnout Inventory – General Survey; Index of Psychological Well-Being at Work; two open questions created by the authors of the study and socio-demographic survey. Based on the results, it was found that there are correlations between variables, namely, a positive relationship between relational authenticity and well-being and a negative – between both exhaustion and cynicism burnout subscales. There are differences in variables between age groups, seniority groups and different types of work models, and the impact of authenticity on both burnout and well-being was found. Results help to draw the attention of employers to promotion of authenticity as a tool for enhancing well-being and preventing burnout, proposals can be used for aforementioned purposes in organizations.